Optimasi Pemanfaatan Air Embung Kasih untuk Domestik dan Irigasi Tetes - Ginting, Segel; Rahmandani, Dadan; Indarta, Abid Hendri (Balai Teknik Irigasi, 2018)
The Government of Indonesian was built Embung Kasih (retention basin) to overcome limited water resources in Tuatuka Village, NTT Province. It was planned for irrigation and domestic use. Retention basin operations require detailed planning with limited storage, so the water utilization optimizes are necessaries. These are needed to determine water use with several scenarios of rainfall conditions. It was conducted by the Generalized Reduced Gradient Method to maximize water use as an objective function. Water utilizes simulation in 1974 to 2015 was conducted as an evaluation of the reliability assessment. The objective of this research determines water used optimally for domestic use and irrigation. The results are obtained by several scenarios. The first scenario related to normal rainfall conditions, water use for domestic is around 2,604 people or irrigating 2.746 ha area using drip irrigation. The second scenario for extreme wet rainfall conditions, water use for domestic is around 3,601 people or land irrigating around 4.698 ha area. The third scenario with extreme dry rainfall conditions can produce water use for domestic is around 454 people or land irrigating around 0.45 ha area. Following their results by using the simulation method with data from 1974 to 2015, water use for domestic is, determined to be around 454 people, and an area irrigated 1 Ha with operational reliability assessment reaching 78.57%.